Hydraulic properties of a geosynthetic composite after mechanical damage and abrasion and their variability - M. Pinho Lopes (2014)
In this paper results of tests to assess the effect of mechanical damage (generally associated with installation processes) and abrasion are presented. Laboratory tests were carried out. The material tested is a composite consisting of two overlapped geosynthetics: a nonwoven geotextile and a woven geogrid. The composite was submitted to each referred agent mechanical damage and abrasion) in isolation and sequentially, in order to assess an eventual synergetic effect. The effect of the damage induced in some physical and hydraulic properties of geosynthetics was assessed: characteristic opening size and permittivity. The variability of these properties was assessed by using either 1 or 3 tests per sample. The results indicate that the number of tests carried out leads to different conclusions, pointing out the need of adjusting the number of specimens to be tested. The mechanical damage seems to result in a significant clogging of the geocomposite's pores, while the abrasion damage resulted in decreased constrictions to the flow of water. Some synergisms were observed for mechanical and abrasion damage.